PENGARUH KONSUMSI DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI KOTA PADANG - Deprianto, Deprianto; Asrizal, Asrizal; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
ABSTRAKAn economic growth means that a development of economy causing to produce the things and services will increase and improve community prosperities. The economic growth of Padang City in the periode of 2001 to 2011 underwent fluctuating changes, so that it is necessary to be further studied on such the causing factors. The purposes of this research are to know the relationship between: (1) Consumption and economic growth, (2) InvestmentÂ  and economic growth, and (3) Simultaneous consumption and investment and economic growth in Padang City.This is a quantitative research and it has been made in Padang City. The data used in this research is secondary data with yearly time series data in the periode of 2001 to 2011, collected from BPS (Statistical Center Board). The variable of this research is an economic growth seen from PDRB according to the constant price of 2000, based on usage, consumption and investment of Padang City. The model of analysis used is double linear regression analysis.The results of research show that (1) the consumption influences significantly the economic growth of Padang City, (2) the investment influences positively significantly the economic growth of Padang City, and (3) the simultaneous consumption and investment induces positively significantly the economic growth of Padang City.